Climatic Impact on Wheat Production in Terai of Nepal - Devkota, Niranjan; Phuyal, Ram Kumar (Journal of Development and Administrative Studies, 2016)
This study examines the climatic impact on wheat production in Terai of Nepal. This paper employs a Ricardian cross-sectional approach to estimates the relationship between wheat production and net revenue associated with wheat production in the plain area of Nepal (i.e. Terai) with different temperatures (average, maximum and minimum), precipitation and other traditional inputs like population density, seed, fertilizer, human labour, bullock labour and tractor. By using district level secondary data of 25 years, this study finds significant positive impact of the average and maximum temperature and significant negative impact of the minimum temperature on net revenue and wheat yield of the Terai region. Similarly, precipitation has mixed impacts. With the maximum temperature, increase in precipitation reduces net revenue and wheat yield whereas with average and minimum temperature, precipitation increases wheat yields as well as revenue. Other traditional inputs like population density, seed, manure, human labour and tractor used are positively associated with climatic change and increase net revenue as well as wheat yield whereas fertilizer and bullock used are negatively associated with climatic change and reduce net revenue and wheat yield. The Journal of Development and Administrative Studies (JODAS), Vol. 23(1-2), pp. 1-22